Experimental evaluation of microscopic pore structure and fluid migration characteristics of coal-measure sandstone reservoirs - Pan, Jishun; Peng, Yicong (Frontiers in Earth Science, 2022)
As a complex multi-media, the microscopic migration characteristics of fluids in coal measure sandstone has always been a hot spot in reservoir evaluation. In this paper, taking the Yan'an Formation sandstone reservoir in Block A of the Ordos Basin as an example, the pore structures and fluid migration characteristics of coal-measure sandstone are systematically studied, using a large number of thin sections, SEM, NMR, relative permeability and water-flooding test results in this area. The research shows that the Jurassic sandstone in the target layer mainly develops lithic quartz sandstone, and the main pore types are intergranular pores and dissolution pores, followed by a small amount of intercrystalline pores. The surface porosity of the target sandstone mainly ranges from 7.9% to 10.79%, with an average value of 8.78%. The good correlation between porosity and permeability indicates that the target layer is a porous reservoir. The T2 relaxation time of the target layer is mainly distributed within 100 ms. The reservoir of Yan'an Formation has high saturation of movable fluid, which is mainly distributed in 43.17%-71.24%, with an average value of 56.90%. Moreover, samples with fractures have higher movable fluid saturation. In addition, the average irreducible water saturation of the Yan'an Formation sandstone reservoir is 35.14%, and the final oil displacement efficiency is 51.14% on average. There is a good positive correlation between oil displacement efficiency and co-permeability zone. As the co-permeability zone range increased from 15% to 55%, the oil displacement efficiency increased from 30% to 65%. When the core contains fractures, it is characterized by high permeability, high oil recovery rate, high oil displacement efficiency in anhydrous period, low irreducible water saturation and low residual oil saturation. This study can provide a reference for the formulation of efficient development plans for sandstone reservoirs.